2013
DOI: 10.14374/hfs.2013.21.2.181
|View full text |Cite
|
Sign up to set email alerts
|

Case Study of the Patient Considering Chronic Renal Failure Treated with Bojungikki-tang and Bojungikki-tang gamibang

Abstract: Objectives : The purpose of this study is to report the clinical effect of herbal medicine on the patient considering chronic renal failure. The patient complained of hemiparesis, general weakness, anorexia, nausea and dizziness. Methods : According to the traditional Korean medicine syndrome differentiation, the patient was classified as Deficiency of Spleen Qi and prescribed Bojungikki-tang and Bojungikki-tang gamibang as well as acupuncture and moxibustion treatment. Changes of BUN, creatinine, VAS for gena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Among these, OR has been reported to prevent renal injury in diabetes-induced renal dysfunction, nephrosis, and hyperuricemic models [ 20 22 ], and systems pharmacology has revealed that its mechanisms of action involve the renin-angiotensin-aldosterone system (RAAS) for treating hypertension [ 23 ]. Case reports for treatments with BJ have shown improved symptoms in patients with chronic renal failure [ 24 , 25 ]. However, there have been few studies on treatments of BJ, PJ, or WR for AKI, to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, OR has been reported to prevent renal injury in diabetes-induced renal dysfunction, nephrosis, and hyperuricemic models [ 20 22 ], and systems pharmacology has revealed that its mechanisms of action involve the renin-angiotensin-aldosterone system (RAAS) for treating hypertension [ 23 ]. Case reports for treatments with BJ have shown improved symptoms in patients with chronic renal failure [ 24 , 25 ]. However, there have been few studies on treatments of BJ, PJ, or WR for AKI, to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%